Public Deliberation on Climate Change: Lessons from Alberta Climate Dialogue - edited by Lorelei L. Hanson (Athabasca University Press, 2018)
There exists in both academic and political circles a growing interest in public deliberation as an alternative to the sometimes adversarial and polarizing public engagement activities that result in the pitting of experts against lay people. Proponents of public deliberation claim that a more deliberative process can engage a diversity of participants in a more guided process that better balances expert knowledge and citizen inclusion. Such an approach holds particular promise where citizens and governments engage in discussions of the most complex and intractable issues like climate change. Given the host of challenges climate governance presents and the global consequences of our response to them, the experience and knowledge shared by Hanson and the contributors to Public Deliberation on Climate Change provide an important framework for advancing public conversations and processes on this and other wicked problems. The lessons contained in the volume were gained as a result of a five year multidisciplinary, community, university research project called Alberta Climate Dialogue (ABCD), which drew together scholars, practitioners, citizens, civil society members, and government officials from across Alberta at four public deliberations. By highlighting the value tensions and trade-offs and examining the impact that the design of the deliberations has on policy and the creation of conditions that encourage exchange, the contributors aim to build capacity within our institutions and society to find new ways to discuss and solve complex problems.